The implications of the COVID-19 pandemic on the mental and physical health of professors in the Medicine course of a university in the metropolitan region of Espírito Santo state, Brazil (Brazilian Journal of Health Research, 2023)
Introduction:The accelerated rise of COVID-19 changed routine and lifestyle of medicine professors, who had to reconcile work on the front line with the change to remote education. Objective: To evaluate the implications of the COVID-19 pandemic on mental and physical health of medicine faculty at a University in the Metropolitan Region of Espírito Santo, Brazil. Methods: This is a cross-sectional, quantitative and qualitative study conducted with medicine professors at a University in the Metropolitan Region of Espírito Santo, Brazil, from August 2020 to December 2020. Data collection was performed with online questionnaire, data entry in Excel 2010 and analysis in OpenEpi. The study was approved by the Ethics Committee on Research with Human Beings of the University in study. Results: It was possible to establish an influence of the pandemic on the level of stress (p
Keywords: Pandemic; COVID-19; Mental health; Lifestyle; Medicine professors